PENDUGAAN CADANGAN KARBON PADA TANAMAN KARET (Hevea brasiliensis Muell. Arg.) DI PERKEBUNAN RAKYAT DESA TAREAN KECAMATAN SILINDAK, KABUPATEN SERDANG BEDAGAI - Frans R Sipayung; Muhdi Muhdi; Diana Sofia Hanafiah (Peronema Forestry Science Journal, 2016)
Global warming is causing an increase in temperature of the earth's atmosphere, climate change, resulting in the dry season and rising temperatures. Efforts to control global warming is with the plant the absorption of carbon. One of which is rubber plant that has a high potential carbon reserve. The purpose of this research want to know the carbon content in each section rubber tree (Hevea brasiliensis Muell. Arg.) and determine the potential of carbon reserves in the rubber tree (Hevea brasiliensis Muell. Arg.) Age of 5 years in people plantation Serdang Bedagai. The method of estimaty carbon stocks done destructive and selection of plant samples carried out with purposive sampling. The carbon content in each section rubber trees (Hevea brasiliensis Muell. Arg.) 5 years of age is different is stem 50.37%, 40.58% branches and leaves 21.68%. The results showed that allometric models for biomass and carbon has W = 3.425 DBH1.153 and C = 0.582 DBH 1.586 , respectively. The potential of biomass and carbon in smallholder rubber plantations Tarean Village, District Silindak, Serdang Bedagai were 2.71 tons / ha and 1.18 tons C / ha, respectively. Keywords: Karet (Hevea brasiliensis Muell. Arg), carbon stocks, biomass measurement, allometric models.